Effectiveness of Modified Hybrid Brainstorming Learning Program in Increasing Innovative Work Behavior and Innovative Idea Performance among Nurses - Kamonmarttayakul, Katekanok; Boonyoung, Nongnut; Phumdoung, Sasitorn (Trends in Sciences, 2021)
The ability to learn and innovate has been known as a key-factor for nurses to deliver quality of care and patient safety. To be successful in nursing innovation, nurses should perform sound innovative behaviors; thus, their innovative work behavior (IWB) should be promoted. A comprehensive learning program aimed at improving IWB with effective cognitive stimulation could enhance innovation abilities and quality of innovative idea performance. This study aimed to evaluate the effectiveness of a learning program that uses Modified Hybrid Brainstorming (MHB) techniques in increasing IWB and improving the quality of ideas generated (fluency, flexibility and originality) among nurses. A sample of 60 nurses were randomly assigned to a within group pre-test and post-test study design. The learning program with the MHB method was developed and implemented for 3 sessions workshop. IWB was measured pre- and 12 weeks post-program. Pre- and post-training session fluency, flexibility, and originality of generated ideas were also measured. The percentage of absolute agreement and the index of item- objective congruence of research instruments were met. Data were analyzed using descriptive statistics, and paired t-test. The results revealed that the average IWB scores of nurses after the implementation of the MHB learning program increased significantly (p < 0.05). There was also a significant difference in post-test scores (p < 0.05) of fluency, flexibility, and originality of ideas. This study showed that offering the MHB learning program to nurses is a feasible method to improve IWB and innovative idea.